Murinization of internalin extends its receptor repertoire, altering Listeria monocytogenes cell tropism and host responses. - Yu-Huan Tsai (Public Library of Science (PLoS), 2013)
Listeria monocytogenes (Lm) is an invasive foodborne pathogen that leads to severe central nervous system and maternal-fetal infections. Lm ability to actively cross the intestinal barrier is one of its key pathogenic properties. Lm crosses the intestinal epithelium upon the interaction of its surface protein internalin (InlA) with its host receptor E-cadherin (Ecad). InlA-Ecad interaction is species-specific, does not occur in wild-type mice, but does in transgenic mice expressing human Ecad and knock-in mice expressing humanized mouse Ecad. To study listeriosis in wild-type mice, InlA has been "murinized" to interact with mouse Ecad. Here, we demonstrate that, unexpectedly, murinized InlA (InlA(m)) mediates not only Ecad-dependent internalization, but also N-cadherin-dependent internalization. Consequently, InlA(m)-expressing Lm targets not only goblet cells expressing luminally-accessible Ecad, as does Lm in humanized mice, but also targets villous M cells, which express luminally-accessible N-cadherin. This aberrant Lm portal of entry results in enhanced innate immune responses and intestinal barrier damage, both of which are not observed in wild-type Lm-infected humanized mice. Murinization of InlA therefore not only extends the host range of Lm, but also broadens its receptor repertoire, providing Lm with artifactual pathogenic properties. These results challenge the relevance of using InlA(m)-expressing Lm to study human listeriosis and in vivo host responses to this human pathogen.